(untitled) (Italian Journal of Public Health, 2010)
Extract:I am very glad to speak about Professor Bruno Angelillo in this occasion (National Conference of Public Health, Naples 2009). Probably Giancarlo De Riu would have done this better of me, but he passed away over two years ago and now I want to associate him in memory with Prof. Angelillo, perhaps for the first time in our academic history. Accepting this task, I realised how emotionally deep and delicate it was, especially considering the professor as the Founder of the Neapolitan School of Hygiene. I hope you will forgive me if in this memory I have necessarily include some personal elements: I will start therefore with a declaration of a heavy conflict of interest! I met professor Angelillo in Cremona, our hometown, before my graduation in Parma. The following March I went for a interview at the Institute of Hygiene of Sassari and in April I moved on a permanent basis to that city! I left behind my student status as a little bit “dispersive”, finding in Bruno Angelillo and Giancarlo De Riu a reference and a guide capable of providing a new order in my life.